An ancient theory of religion: Euhemerism from antiquity to the present - Roubekas, Nickolas P. (Routledge monographs in classical studies, 2017)
"This book examines Euhemerism - a theory of religion developed by Euhemerus of Messene in the late 4th through early 3rd centuries BCE - tracing the history and reception of the theory in antiquity and in early Christianity, where it was adopted and reshaped for particular religious and ideological reasons. It shows how and why Euhemerism arose, how it was used, and how it significantly influenced theoretical discussions of religion from antiquity onward."--